STUDY ON THE POWER – ENERGETIC INDICATORS OF A UNIVERSAL MILLING MACHINE (Innovation in Woodworking Industry and Engineering design, 2026)
Experimental studies during milling of solid wood were carried out. The current study was performed at the Laboratory of Woodworking Machinery, University of Forestry, Sofia. The measurements were carried out using universal milling machine FD – 3 (ZDM – Plovdiv). The correlations between fundamental factors influencing the milling process and target functions, such as cutting force and power, specific cutting work, specific power consumption have been investigated. On the basis of the analysis of the obtained results, practical recommendations have been proposed.